2020
DOI: 10.3897/zookeys.974.56070
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new horned toad of Megophrys Kuhl & Van Hasselt, 1822 (Anura, Megophryidae) from southwest China

Abstract: A new species of the genus Megophrys is described from Guizhou Province, China. Molecular phylogenetic analyses supported the new species as an independent clade nested into the Megophrys. The new species could be distinguished from its congeners by a combination of the following characters: body size moderate (SVL 49.3–58.2 mm in males); vomerine ridges present distinctly, vomerine teeth present; tongue feebly notched behind; tympanum distinctly visible, oval; two metacarpal tubercles in hand; toes with one-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“… Panophrys congjiangensis sp. nov. is assigned to the genus Panophrys based on molecular phylogenetic analyses and the following characteristics, which are diagnostic for this genus: (1) snout shield-like; (2) snout projecting beyond the lower jaw; (3) tympanum distinct (4) canthus rostralis distinct; (5) chest gland small and round, closer to axilla than to midventral line; (6) femoral gland on rear of thigh; (7) vertical pupils (Fei et al 2006; Fei and Ye 2016 ; Su et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Panophrys congjiangensis sp. nov. is assigned to the genus Panophrys based on molecular phylogenetic analyses and the following characteristics, which are diagnostic for this genus: (1) snout shield-like; (2) snout projecting beyond the lower jaw; (3) tympanum distinct (4) canthus rostralis distinct; (5) chest gland small and round, closer to axilla than to midventral line; (6) femoral gland on rear of thigh; (7) vertical pupils (Fei et al 2006; Fei and Ye 2016 ; Su et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Panophrys congjiangensis sp. nov. does not belong to any of the clades identified by Chen et al (2017) and Liu et al (2018) , suggesting that Panophrys diversity may remain severely underestimated, even where Panophrys species are sympatric ally distributed (Li et al 2018; Lyu et al 2020 ; Su et al 2020 ). Until recently, it was difficult to perform taxonomic and phylogenetic studies of the Panophrys because many species in this genus are morphologically similar and have sympatric distributions; the many possible cryptic species in the Panophrys may have hindered our understanding of diversity in this genus ( Chen et al 2017 ; Liu et al 2018 ; Li et al 2018; Wang et al 2019a , b ; Mahony et al 2020 ; Lyu et al 2020 ; Liu et al 2020 ; Xu et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the findings of the new species also indicated a high degree of localised diversification and micro-endemism for the species in the genus Leptobrachella because in Guizhou Province, China, the five recent-described Leptobrachella species are just known only from their type localities or nearby areas. In addition, in recent years, large number of discoveries have been made from Guizhou, dramatically raising the number of frog species known from the region ( Zhang et al 2017 ; Li et al 2018a , b , 2019a , b , 2020a , b , c ; Lyu et al 2019 ; Wang et al 2019 ; Luo et al 2020 ; Su et al 2020 ; Xu et al 2020 ; Wei et al 2020 ). This further indicated that more investigations should be conducted in Guizhou Province to define more precisely distribution area of the new species and detect more cryptic species especially in the poorly-investigated areas.…”
Section: Discussionmentioning
confidence: 99%